Hang on a Sec! Effects of Proactive Mediation of Phone Conversations while Driving - Iqbal, Shamsi; Horvitz, Eric; Ju, Y.C.; Mathews, Ella; Ju, Y. C. (ACM Conference on Human Factors for Computing Systems (CHI), 2011)
Conversing on cell phones while driving is a risky, yet commonplace activity. State legislatures in the U.S. have enacted rules that limit hand-held phone conversations while driving but that allow for hands-free conversations. However, studies have demonstrated that the cognitive load of conversation is a significant source of distraction that increases the likelihood of accidents. We explore in a controlled study with a driving simulator the effectiveness of proactive alerting and mediation of communications during phone conversations while driving. We study the use of auditory messages indicating upcoming critical road conditions and placing calls on hold. We found that such actions reduce driving errors and that alerts sharing details about situations were more effective than general alerts. Drivers found such a system valuable in most situations for maintaining driving safety. These results provide evidence that context-sensitive mediation systems could play a valuable role in focusing drivers‟ attention on the road during phone conversations.
Received Honorable Mention award